2010
DOI: 10.2214/ajr.09.3319
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of CT Density in Patients With Diffusely Increased FDG Uptake in the Thyroid Gland on PET/CT Images

Abstract: CT density is closely related to FDG uptake, and low CT density coupled with high FDG uptake suggests a change in thyroid tissue composition and is probably helpful for assessing the disease process and thyroid function of patients whose thyroid show diffuse FDG uptake on FDG PET/CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
3
19
0
Order By: Relevance
“…Because colloid volume is about 3 times greater than the epithelial cell volume, 18 the high electron density of the iodine colloid leads the high attenuation of the thyroid on MDCT. [19][20][21] Our results are confirmed in a report by Han et al, 22 who studied the appearance of the thyroid gland using PET/CT. They found that thyroid density is proportional to colloid volume and inversely proportional to the cellular component of the thyroid and FDG avidity.…”
Section: Discussionsupporting
confidence: 88%
“…Because colloid volume is about 3 times greater than the epithelial cell volume, 18 the high electron density of the iodine colloid leads the high attenuation of the thyroid on MDCT. [19][20][21] Our results are confirmed in a report by Han et al, 22 who studied the appearance of the thyroid gland using PET/CT. They found that thyroid density is proportional to colloid volume and inversely proportional to the cellular component of the thyroid and FDG avidity.…”
Section: Discussionsupporting
confidence: 88%
“…This may be explained by the fact that the measurement of thyroid tissue by the CT value can only partly reflect the iodine content of the thyroid, and it may also be affected by the density of thyroid tissue. Studies have shown that different thyroid disease tissues have different CT values, and in most cases, the CT values of thyroid disease tissues are lower than those of normal thyroid tissues [15,16]. Therefore, compared with the CT value, the measurement of the iodine concentration and iodine content has more advantages in determining the pathological changes of thyroid tissue and iodine ion content in the thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the fact that the measurement of thyroid tissue by the CT value can only partly reflect the iodine content of the 8 thyroid, and it may also be affected by the density of thyroid tissue. Studies have shown that different thyroid disease tissues have different CT values, and in most cases, the CT values of thyroid disease tissues are lower than those of normal thyroid tissues [15,16] . Therefore, compared with the CT value, the measurement of the iodine concentration and iodine content has more advantages in determining the pathological changes of thyroid tissue and iodine ion content in the thyroid.…”
Section: Discussionmentioning
confidence: 99%